Sistem Layanan Informasi Akademik Menggunakan Chatbot Whatsapp - Adhy Rizaldy; Andi Muhammad Nur Hidayat; Ilma Permata Dwitami (Subaltren Inti Media, 2024)
Academic information services are information services that are very important for the academic community, and greatly affect student satisfaction in their use because the management of information data for academics is something that is absolutely necessary for educational institutions such as universities.The purpose of this research is to create a new academic information service that will be developed using chatbots on the WhatsApp application, especially in the UIN Alauddin Makassar Information Systems Study Program. Academic information services were developed to be able to access information for members of the Information Systems study program such as student status (view student status), payment (view payment status), KRS (view KRS status), schedule (view class schedule), IPS (see history IPS), Ipk (see GPA history. The type of research used is applied research with a quantitative approach. System development uses the waterfall method, then the system is designed using Unified Modeling Language (UML) data. The programming language used is JavaScript. System testing with Black box testing.Research conducted to create an academic information service system using chatbots has a good effect of 76.4% on the ease of obtaining inform